Modeling dynamicity of willingness to pay mechanism in the case of special assessment district - Bae, Deog Sang; Kim, Seok (International Journal of Strategic Property Management, 2020)
A new public project usually provides economic benefits to property owners. In general, a delay caused by a government budget shortage proportionally reduces the future cash flow of the private developer potentially benefitted from a new public project. Based on that eventuality, this study examines a mechanism of willingness to pay, which asks private developers to voluntarily participate in sharing the budget shortage. This participation process is investigated by applying system dynamics, which demonstrate several causal loops, such as between the delay cause and the reaction of the private developer. In spite of difficulty in predicting the actual effect of this idea due to its conceptual origin, this innovative approach can contribute to real-world exigencies in two ways: the provision of background for research on the on-time completion of public projects via private developer cost-sharing participation and the illustration of an alternative that minimizes private developers’ future revenue deduction caused by delays.First published online 23 June 2020